A Frontal Dust Storm in the Northern Hemisphere at Solar Longitude 97—An Unusual Observation by the Emirates Mars Mission. Issue 20 (18th October 2022) - Gebhardt, C.; Guha, B. K.; Young, R. M. B.; Wolff, M. J.
Abstract: The Emirates Mars Mission (EMM) science phase began in Martian Year 36, solar longitude 49, which is outside of the classical Mars dust storm season. EMM observed a distinct dust cloud at northern mid‐to‐high latitudes on 10 September 2021 (Martian Year 36, solar longitude 97). The dust cloud is an arc‐shaped dust storm, typically observed at the northern polar cap edge. This type of non‐season dust storm is a well‐known phenomenon, but this particular case is interesting because the dust cloud has frontal structure. A large atmospheric front is unusual in this location and season. Moreover, EMM's unique observational coverage adds value to this observation. EMM provided a sequence of four camera images, which are separated by just 2–3 hr. The dust cloud showed very little motion over 7–8 hr, that is, it is quasi‐stationary. We discuss relevant dynamical processes, supported by a consistency check with the Mars Climate Database. Plain Language Summary: The Emirates Mars Mission (EMM) officially started its science observations on 23 May 2021. We saw some, but not many dust storms until end of 2021. That is because Mars has a dust storm season and a non‐dust‐storm‐season, and EMM arrived during the latter. On 10 September 2021, EMM observed an arc‐shaped dust storm close to the northern polar cap. This type of non‐season dust storm is well‐known. What makes this observation interesting is that the dust storm is also a weather front. A large atmospheric front is unusual for this location and time during the Martian year. Moreover, it is unique how EMM observed this dust storm. EMM took a camera image every 2–3 hr, giving four dust cloud images in total. The dust cloud showed very little motion over 7–8 hr. We discuss how the motion of air masses in the Mars atmosphere may have caused the observed dust storm. The discussion is supported by wind and temperature data from the Mars Climate Database. Key Points: We study a sequence of four Emirates Mars Mission images, showing a frontal dust cloud on 10 September 2021 (solar longitude 97) The dust cloud extends from the Chasma Boreale of the northern polar cap to the midlatitudes; it shows very little movement for 7–8 hr Large atmospheric fronts are unusual in this location and season; we discuss dynamical processes, supported by the Mars Climate Database